Utilização de bacteriófagos ambientais no controle de biofilmes de Salmonella spp. em superfícies utilizadas na indústria de processamento e comercialização de frango de corte e derivados - Garcia, Keila Carolina de Ornellas Dutka [UNESP] (2015)
Biofilm is a major source of food contamination and may be present in various parts of the chicken meat processing chain. The control of biofilm in the food industry needs alternative methods in order to overcome resistance to disinfectants and ensure food free of chemical residues. The objective of this study was to evaluate the influence of the surfaces of stainless steel, glass and PVC in the biofilm formation by Salmonella spp. at different times and evaluate the action of a pool of bacteriophages against this bacterial biofilms. Most samples were classified as weak biofilm producers. Heidelberg and Enteritidis serotypes showed a significantly higher number of samples capable to produce biofilm. The surfaces of stainless steel and glass significantly favored the biofilm formation in three and five periods, respectively. The bacteriophage pool reduced biofilm formation on the surfaces of stainless steel, glass and PVC and its action period focused mainly at 3h. Our findings suggests that there is a difference in the production of biofilms by different serotypes of Salmonella spp., as well as significantly interference of the surfaces in the production of biofilms by this bacteria, however more studies should be conducted in order to characterize the bacteriophage action in the control of biofilms